Sentinel lymph node localization with contrast-enhanced ultrasound and an I-125 seed: An ideal prospective development study. (February 2015) - Barentsz, M.W.; Verkooijen, H.M.; Pijnappel, R.M.; Fernandez, M.A.; van Diest, P.J.; van der Pol, C.C.; Witkamp, A.J.; Hobbelink, M.G.G.; Sever, A.R.; van den Bosch, M.A.A.J.
Abstract: Introduction: Our aim was to evaluate the development of microbubble-enhanced sentinel lymph node (SLN) localization with placement of an I-125 seed in breast cancer patients as a potential alternative for SLN localization with nanocolloid. The study is conducted and reported following the IDEAL recommendations for evaluation of a new technique at Stage 2a (Prospective Development Study). Methods: Fourteen consecutive patients with 15 lesions underwent microbubble-enhanced SLN localization with placement of an I-125 seed after the standard SLN localization (nanocolloid). We placed an I-125 seed within or near the SLN following its identification using intradermally injected microbubbles. The SLN was excised guided by nanocolloid and the SLN containing the I-125 seed was searched for. All technical modifications are described and standardized outcomes measured. Results: Twelve (80%) microbubble procedures with I-125 seed placements were technically successful. In three cases no microbubble-enhancing lymph node could be detected. Intraoperatively, we found nine I-125 seeds within 0.5 cm of the nanocolloid confirmed SLN. One I-125 seed was found next to a non-SLN and two I-125 seeds were not near any lymph node. Overall, the procedure was successful in 60% (9 out of 15) of the cases. Conclusion: Given the low success rate, we conclude that microbubble-enhanced SLN is not a viable alternative to the standard SLN procedure. Modifications to this technique did not improve its performance. Planned study (NTR3690http://www.trialregister.nl/trialreg/admin/rctview.asp?TC=3690 ) was stopped early due to this conclusion and results reported in order to provide a full and transparent record of the evolution of technique. Highlights: The current SLN procedure with nanocolloid is very accurate, though logistically complicated and time consuming. A new SLN procedure with microbubbles and an I-125 seed can be performed days or weeks before the surgical SLN procedure. SLN localization with microbubbles and an I-125 seed proved not to be a viable alternative to the standard SLN procedure. Modifications to this technique did not improve its performance.